Effects of benzylaminopurine (BAP) concentrations on proliferation of dendrobium hybrid orchid and arundina graminifolia - Bong, Fui Joo (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Dendrobium hybrid orchid and Arundina graminifolia are valuable flowering plants that have been used for cut flower industry due to their attractive and long lasting flower. However, their propagation rate under conventional methods is slow and unable to meet the increased demand of plantlets. This study was conducted to determine the best concentration of BAP for developing an efficient protocol for mass production of planting materials. Young leaves excised from the mother plant of Dendrobium and protocorms of A. graminifolia produced from in vitro germinated seeds were selected as the explants and inoculated on MS medium supplemented with BAP at different concentrations (0.5, 1.0, 1.5, 2.0 and 2.5 mg/L). The results obtained showed that the protocorms of A. graminifolia were proliferated on all tested media where the highest percentage of proliferation was found on MS medium containing 1.5 mg/L BAP (33.3316.67%) with an average of 7.00 ± 2.00 new protocorms formed per protocorm at 60 DAC. For Dendrobium, the leaf explants only changed their colour from green to yellowish or brownish instead of proliferating or PLBs formation at 60 DAC on all tested media.